1997
DOI: 10.1046/j.1471-4159.1997.68020750.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Temporal Analysis of Events Associated with Apoptosis Induced by Lowering the Extracellular Potassium Concentration in Mouse Cerebellar Granule Neurons

Abstract: Abstract:We analyzed biochemically and temporally the molecular events that occur in the programmed cell death of mouse cerebellar granule neurons deprived of high potassium levels. An hour after switching the neurons to a low extracellular Kconcentration ([K~] 0),a significant part of the genomic DNA was already cleaved to highmolecular-weight fragments. This phenomenon was intensified with the progression of the death process. Addition of cycloheximide to the neurons 4 h after high [K~]0 deprivation resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 38 publications
5
54
1
Order By: Relevance
“…1c) because, at that time, genes necessary to apoptosis induction have already been expressed. Our data were consistent with results reported by others in mouse CGN (17): transcriptional and translational commitment points were ϳ5 h after deprivation. The temporal curves of apoptosis (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1c) because, at that time, genes necessary to apoptosis induction have already been expressed. Our data were consistent with results reported by others in mouse CGN (17): transcriptional and translational commitment points were ϳ5 h after deprivation. The temporal curves of apoptosis (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, we have shown that there is a loss of mitochondrial function (as assessed by CMTMR accumulation) associated with ara C-induced apoptosis but not low K~-induced apoptosis. The latter result appears to contradict the findings of Nardi et al (1997), who reported that there is a rapid loss of ATP and mitochondrial function [assessed by 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide assay] following K + withdrawal from mouse cerebellar granule cells, but there are several major differences between the studies. Nardi et a!.…”
Section: Discussioncontrasting
confidence: 61%
“…1), and in our studies we found that K~withdrawal while serum was maintained produced a slower, less extensive degree of apoptosis. Because Nardi et al (1997) reported that decreases in ATP levels follow but occur later than the loss of neuronal viability and we see no change in CMTMR accumulation in low K + -induced apoptosis, it is likely that the commitment to apoptosis following K + withdrawal does not involve or does not depend on a loss of mitochondrial function. The ara C-induced apoptosis, however, does involve a loss of mitochodrial function early in the apoptotic process (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…This neuronal death occurs by a sequence of apoptosis-autophagy and necrosis phenomena and is hampered when neurons are grown in medium containing depolarizing levels of potassium (25 mM KCl) or moderate concentration of NMDA. It is assumed that both factors, through different signal transduction pathways, mimic the pro-survival electrical stimulation from afferent synapses (Gallo et al, 1987;D'Mello et al, 1993;Nardi et al, 1997;Xifro et al, 2005). NMDAR-mediated prosurvival activity is, in part, mediated through the activation of PI3K and MAPK pathways (Zhang et al, 1998;Hetman & Kharebava, 2006).…”
Section: Introductionmentioning
confidence: 99%